2023
DOI: 10.3390/biomedicines11030837
|View full text |Cite
|
Sign up to set email alerts
|

Parsonage-Turner Syndrome Following SARS-CoV-2 Infection: A Systematic Review

Abstract: Parsonage-Turner syndrome (PTS) is an inflammatory disorder of the brachial plexus. Hypothesized underlying causes focus on immune-mediated processes, as more than half of patients present some antecedent event or possible predisposing condition, such as infection, vaccination, exercise, or surgery. Recently, PTS was reported following the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We aimed to investigate data on PTS triggered by SARS-CoV-2 infection to provide an extensive perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
(452 reference statements)
1
9
2
Order By: Relevance
“…In most cases, further PTS symptoms appeared within two weeks after the onset of pain; only two patients with a history of viral vector vaccination presented motor and sensory signs after three weeks [ 42 ] and one month, respectively [ 44 ]. These findings contrast the data from the literature, including patients with or without COVID-19, where authors found that in 27.2% [ 1 ] and 25% [ 62 ] of cases, paresis did not manifest itself until over two weeks later [ 1 ].…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…In most cases, further PTS symptoms appeared within two weeks after the onset of pain; only two patients with a history of viral vector vaccination presented motor and sensory signs after three weeks [ 42 ] and one month, respectively [ 44 ]. These findings contrast the data from the literature, including patients with or without COVID-19, where authors found that in 27.2% [ 1 ] and 25% [ 62 ] of cases, paresis did not manifest itself until over two weeks later [ 1 ].…”
Section: Discussioncontrasting
confidence: 93%
“…In the mRNA group, 64% of cases were males, similar to other cohorts from the literature, including PTS of all causes [ 1 ]. The proportion of males in the viral vector group was higher (83.3%), comparable to the gender distribution reported by a previous systematic review on PTS following SARS-CoV-2 infection [ 62 ]. A family history was absent in all patients, but most authors did not report on it.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations